ETV5 cooperates with LPP as a sensor of extracellular signals and promotes EMT in endometrial carcinomas - Colas, E. (2012)
Endometrial carcinoma (EC) is the most frequent among infiltrating tumors of the female genital tract, with myometrial invasion representing an increase in the rate of recurrences and a decrease in survival. We have previously described ETV5 transcription factor associated with myometrial infiltration in human ECs. In this work, we further investigated ETV5 orchestrating downstream effects to confer the tumor the invasive capabilities needed to disseminate in the early stages of EC dissemination. Molecular profiling evidenced ETV5 having a direct role on epithelial-to-mesenchymal transition (EMT). In particular, ETV5 modulated Zeb1 expression and E-Cadherin repression leading to a complete reorganization of cell-cell and cell-substrate contacts. ETV5-promoted EMT resulted in the acquisition of migratory and invasive capabilities in endometrial cell lines. Furthermore, we identified the lipoma-preferred partner protein as a regulatory partner of ETV5, acting as a sensor for extracellular signals promoting tumor invasion. All together, we propose ETV5-transcriptional regulation of the EMT process through a crosstalk with the tumor surrounding microenvironment, as a principal event initiating EC invasion.